(untitled) (Research, Society and Development, 2022)
Comparative pH analyses were performed on sparkling and mineral water by three distinct methods: pH meter, pH indicator strips, and a universal pH indicator; to present an investigation as a proposal to aid teaching Acid-Base theories for undergraduate students using “Chemistry behind carbonated waters” as theme. Thus, pH values for carbonated and mineral waters were measured and compared with those described in the label, and a discussion was presented for each method employed to gauge pH. A discussion was held to bring students different, more comprehensive acid-base concepts, aiming to expand their knowledge of the subject, and introduce them to new subjects, starting from a simple pH measurement and reaching the calculations required to determine the content of CO2 dissolved in carbonated water samples. Furthermore, data were compared with the current legislation to avoid fraud. Hence, our paper covers acid-base concepts and expands this subject to other areas of chemistry by utilizing contextualization as a teaching strategy.